The Effect of Infiltration Temperature on the Microstructure and Magnetic Levitation Force of Single-Domain YBa2Cu3O7-x Bulk Superconductors Grown by a Modified Y+011 IG Method - Nuerseman Maimaiti; Abulizi Abulaiti; Wanmin Yang (Nanomaterials)
During the preparation of single-domain (S-D) REBa2Cu3O7-x (RE-123) superconducting bulks, the seed crystals can serve as templates for crystal growth, guiding the newly formed crystals to grow in a specific direction, thereby ensuring the consistency of the crystal orientation within the sample. However, the infiltration temperature is typically restricted to approximately 1050 °C when employing NdBa2Cu3O7-x (Nd-123) crystal seeds in the traditional top-seeded infiltration growth (TSIG) technique for producing single-domain Y-123 bulk superconductors. In the present study, to overcome the temperature limitations of the heat treatment process, the optimized Y2O3 +011 IG (011 refers to BaCuO2 powder) method was employed to fabricate a group of single-domain Y-123 bulks with a high-temperature infiltration (1000–1300 °C). The reason for the differences in the superconducting properties between the different samples was analyzed by studying the relationship between the microstructure of the infiltrated pellet and the final Y-123 sample. The research findings were as follows: (1) when the infiltration temperature exceeded 1150 °C, the successful preparation of single-domain YBa2Cu3O7-x (Y-123) bulks became unattainable due to the coarsening or melting decomposition of the Y2BaCuO5 (Y-211) phase according to the SEM–EDS analysis; (2) the content of the Y-211 phase within the Y-123 matrix was approximately 40.8%, 37.2%, 32.7%, 30.5%, and 46.4% for the different final samples; (3) with an increasing infiltration temperature, the magnetic levitation forces exhibited an initial increase followed by a subsequent decline. The maximum levitation force of 47.1 N at 77 K was reached in the sample S3 infiltrated at 1100 °C.